Dinamika Kerja Tim dan Proses Produksi Desain Grafis pada Agensi Kreatif Clico di Kota Pontianak dan Kabupaten Kubu Raya - Buntoro Suakan; Adiel Jonathan Immanuel Purba (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of the local creative industry requires creative agencies to effectively manage team dynamics in order to cope with the fast-paced graphic design production process. This study aims to analyze the dynamics of creative teamwork in the graphic design production process at Clico Creative Agency in Pontianak City and Kubu Raya Regency. This study employs a qualitative descriptive approach. The main theory used is team effectiveness. Data were collected through observation, semi-structured interviews, and documentation involving the owner, graphic designers, and photographers/videographers directly involved in the production process. The results indicate that a semi-matrix team structure with clearly defined roles supports the effectiveness of creative teamwork. Open communication and cross-functional coordination play an important role in translating client briefs into appropriate visual concepts. The graphic design production process is carried out iteratively through the stages of briefing, concept development, production, revision, and finalization. Leadership involvement at the conceptual stage and final evaluation contributes to maintaining visual quality and consistency. This study concludes that effective team dynamics have a significant influence on the smoothness of the production process and the quality of graphic design outputs.